2005
DOI: 10.1371/journal.pgen.0010056.eor
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of human inversion polymorphisms by comparative analysis of human and chimpanzee DNA sequence assemblies

Abstract: With a draft genome-sequence assembly for the chimpanzee available, it is now possible to perform genome-wide analyses to identify, at a submicroscopic level, structural rearrangements that have occurred between chimpanzees and humans. The goal of this study was to investigate chromosomal regions that are inverted between the chimpanzee and human genomes. Using the net alignments for the builds of the human and chimpanzee genome assemblies, we identified a total of 1,576 putative regions of inverted orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…The proximal breakpoint is located in a long terminal repeat. Previous analysis of cytogenetic and submicroscopic inversion breakpoint regions show that repetitive elements, high sequence similarity to the opposite breakpoint, pseudogenes, gene desserts, segmental duplications and co-localization with fragile sites are over-represented [Feuk et al, 2005;Schmidt et al, 2005;Tuzun et al, 2005]. Although both breakpoints identified in our study are located within or adjacent to repeats, they showed no strong homologies to each other from sequence analysis.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The proximal breakpoint is located in a long terminal repeat. Previous analysis of cytogenetic and submicroscopic inversion breakpoint regions show that repetitive elements, high sequence similarity to the opposite breakpoint, pseudogenes, gene desserts, segmental duplications and co-localization with fragile sites are over-represented [Feuk et al, 2005;Schmidt et al, 2005;Tuzun et al, 2005]. Although both breakpoints identified in our study are located within or adjacent to repeats, they showed no strong homologies to each other from sequence analysis.…”
Section: Discussioncontrasting
confidence: 57%
“…Detailed structural analysis of submicroscopic inversion variants indicates that they frequently origin from non-allelic homologous rearrangements between repeated and re-iterated sequences or duplicons [Shaw and Lupski, 2004;Bansal et al, 2007]. Recent progress in genomics indicates that most polymorphic inversions span minor regions down to a few kilobases of DNA [Feuk et al, 2005;Tuzun et al, 2005]. These inversions constitute a large part of the normal genomic variation among humans and may occur frequently as somatic events [Flores et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Other than sequence variants, structural polymorphisms such as copy number variants (including insertions, deletions, and duplications) and copy-neutral genomic rearrangements (such as translocations and inversions) play major roles in human biology and health (Stankiewicz and Lupski 2010;Alkan et al 2011). Indeed, polymorphic rearrangements are a common feature of the human genome (Pang et al 2010) and are implicated in speciation (Feuk et al 2005;Zody et al 2008), population diversification (Stefansson et al 2005;Alves et al 2014), and many complex diseases, including neurological disorders and cancers (Antonarakis et al 1995;Bondeson et al 1995;Koolen et al 2006;Shaw-Smith et al 2006;Sharp et al 2008;Tam et al 2008;Antonacci et al 2009;Salm et al 2012). However, few human inversions have been studied comprehensively to date, and the phenotypic consequences and clinical relevance of most remain undefined (Feuk 2010;Alkan et al 2011;Alves et al 2012;Martinez-Fundichely et al 2014).…”
mentioning
confidence: 99%
“…However, their results were not placed in the DGV. 100 This, together with the study by Feuk et al (2005) 99 , also provided some supporting evidence that a considerable portion of their detected inversions were flanked by highly homologous repeats or segmental duplications. This suggests that segmental duplications could be the favorite spots mediating the chromosomal rearrangements that generate inversions.…”
Section: Copy Neutral Variations-inversions and Translocationsmentioning
confidence: 64%
“…Rather, several different strategies and approaches have been taken to try to identify inversions in the human genome. For example, Feuk et al 99 discovered regions that are inverted between the chimpanzee and human genomes by performing comparative analysis of their DNA sequence assemblies. In the study, they identified about 1600 putative regions of inverted orientation in the genomes that covered 4150 megabases of DNA sequence.…”
Section: Copy Neutral Variations-inversions and Translocationsmentioning
confidence: 99%